2020
DOI: 10.1136/bmjno-2020-000053
|View full text |Cite
|
Sign up to set email alerts
|

Association of cerebral blood flow with myelin content in cognitively unimpaired adults

Abstract: BackgroundMyelin loss and cerebral blood flow (CBF) decline are central features of several neurodegenerative diseases. Myelin maintenance through oligodendrocyte metabolism is an energy-demanding process, so that myelin homeostasis is particularly sensitive to hypoxia, hypoperfusion or ischaemia. However, in spite of its central importance, little is known about the association between blood supply and myelin integrity.Object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 38 publications
(60 reference statements)
3
24
0
Order By: Relevance
“…To address these limitations, we studied a larger cohort, with an improved age distribution, of cognitively unimpaired subjects (N = 140) across the extended age range of 21-94 years. Our main objectives are: First, building on Lambert et al and our previous work [10,15], we sought to characterize age-and sex-related microstructural correlates by determining the diffusion tensor imaging (DTI) indices of fractional anisotropy (FA) and mean, radial, and axial diffusivities (MD, RD, and AxD), as well as longitudinal and transverse relaxation rates (R1, R2), and myelin water fraction (MWF) quantification using our recently-introduced method [16][17][18][19][20][21], within selected brainstem substructures. Second, we compared MWF estimates with widely used markers of myelin content (RD, R1, R2), axonal damage (AxD), and tissue composition (FA, MD) to determine whether the information provided by these biomarkers is complimentary or is redundant to MWF.…”
Section: Introductionmentioning
confidence: 99%
“…To address these limitations, we studied a larger cohort, with an improved age distribution, of cognitively unimpaired subjects (N = 140) across the extended age range of 21-94 years. Our main objectives are: First, building on Lambert et al and our previous work [10,15], we sought to characterize age-and sex-related microstructural correlates by determining the diffusion tensor imaging (DTI) indices of fractional anisotropy (FA) and mean, radial, and axial diffusivities (MD, RD, and AxD), as well as longitudinal and transverse relaxation rates (R1, R2), and myelin water fraction (MWF) quantification using our recently-introduced method [16][17][18][19][20][21], within selected brainstem substructures. Second, we compared MWF estimates with widely used markers of myelin content (RD, R1, R2), axonal damage (AxD), and tissue composition (FA, MD) to determine whether the information provided by these biomarkers is complimentary or is redundant to MWF.…”
Section: Introductionmentioning
confidence: 99%
“…All of the aforementioned pathophysiological alterations resulted in cerebral hypoperfusion. Cerebral hypoperfusion produced pathological myelin loss and axonal injury, altered nerve cell metabolism, promoted neurodegeneration, caused white matter bundle ischemia, disrupted subcortical circuits, and eventually resulted in abnormalities in brain tissue microstructure ( 20 , 52 , 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Active demyelination is associated with a complex pro-inflammatory cascade that has been shown to correlate negatively with CBF alterations. 28 A recent study in healthy cognitively unimpaired adults showed a correlation between CBF and myelin water fraction (MWF) 29 such that as WM microstructural integrity decreased, concomitant decreases in CBF were observed. We found a correlation between capillary-sized cerebral perfusion metrics and WM microstructural integrity assessed using sT 1 w/T 2 w ratios.…”
Section: Discussionmentioning
confidence: 99%